'Chicken and Duck Talk': Life and Death of Language Training at a Japanese Multinational in China. (October 2018) - Zheng, Yu; Smith, Chris
This article examines social relations in language learning through a case study of two cohorts of Chinese workers in a Japanese multinational company (MNC). The two cohorts weigh learning Japanese in the context of internal and external opportunities, and pursue different strategies – deliberative acquisition and deliberative opposition. Exploring the broader meanings of language learning beyond skill acquisition, the article suggests that language is more than an individual asset or a common code for workers to build collective power. Social reproduction of language is embedded in workers' choice of pathways for social mobility which was created in the social transition and has shifted over time in China. These findings make a contribution to the sociology of language training in work, by challenging structural and cultural theories that underplay the agency of workers in assessing language as a resource for labour power development.